Impact of the Covid-19 Pandemic on the Elementary School Student’s Learning Media: A Relationship Between Facilities and Teacher’s Perception - Iqbal Miftakhul Mujtahid; Gandring Vemberia Ismayanti; Musa Thahir; Miftah Audhiha; Rian Vebrianto (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aimed to examine the relationship between facilities and instructors' perceptions of their ability to develop instructional media during a pandemic. This study employed a quantitative approach through the use of a survey. The sample size for this study was 154 elementary school teachers drawn through a purposive sampling technique from Pelalawan and Rengat districts. The data were gathered via a survey administered over WhatsApp and analyzed descriptively and inferentially using SPSS version 26. The findings indicated that all fundamental support facilities for online learning were met 100 % of the time, interactive learning media facilities were met 48.7 % of the time, and assistive devices for students were met 58.4 % of the time. Additionally, 60.4 % of teachers frequently create learning media on their own, 45.5 % frequently generate media independently, and 42.9 % frequently use online learning media. The Pearson Product Moment Correlation Coefficient calculated between facilities and teachers' abilities indicated a significant value of 0.0000.05. As a result, it is possible to conclude that there is a positive and significant association between facilities and the teacher's opinion of their ability to produce instructional media.